National Cultural Features of Toponyms - Samanova Shahlo Bahtiyarovna (International Journal on Integrated Education, 2022)
The article deals with the analysis of English toponymic phraseological units in the context of their reflection of the picture of the world of the English-speaking society. Its relevance is due to the need to study the cultural factor in the language in the framework of linguistic research. However, toponymic phraseological units are extremely rarely studied, despite the fact that it is the toponym, which is part of the phraseological turnover, that is the linguistic sign that transmits information about the history, traditions, values of the culture of the people to future generations.